Economic and Digital Literacy for Community Empowerment in Lumbung Mataraman Tourism - Purbaningrum, Catarina Wahyu Dyah; Putri, Ranny Ismawati (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2026)
This study aims to examine the simultaneous and partial effects of economic literacy and digital literacy on the empowerment of local communities at the Lumbung Mataraman tourist attraction. The research method used was quantitative. The study population included 4,405 residents, with 115 of them being part of the sample. Then, we tested the data to make sure it was valid and that it followed a normal distribution. The results passed all statistical tests. The correlation coefficient analysis shows a weak relationship. However, there is a good connection between economic literacy and digital literacy with community empowerment. The test shows that economic literacy does not have much of an effect on empowerment, but digital literacy does. Together, these two things have a big impact on empowerment. It was concluded that empowerment is more effective when combined with digital literacy. However, economic literacy also plays a supporting role in empowering the local community at the Lumbung Mataraman tourist attraction.